"Watchful observation" follow‐up scheme after endoscopic CO2 laser treatment for small glottic carcinomas: A retrospective study of 93 cases. (24th April 2017) - Gallet, P.; Rumeau, C.; Nguyen, D.T.; Teixeira, P.A.; Baumann, C.; Toussaint, B.
Abstract: Objectives: Evaluate the clinical outcome of patients treated with CO2 laser surgery for early‐stage glottic carcinomas followed up with 3‐month laryngoscopy regardless of tumor grade and margins. Design: Case series. Setting: Retrospective review of the clinical records of patients treated at the ENT department of a tertiary university hospital. Participants and method: Clinical records from patients with early‐stage glottic carcinomas (Tis/T2) treated with curative intent by CO2 laser surgery in a ten‐year period were evaluated. Regardless of tumor margin status, patients underwent fiber endoscopy 6 weeks after surgery and a systematic second look by direct laryngoscopy under general anesthesia at 3 months. Main outcome measures: Local control, laryngeal preservation rate. Results: Ninety‐three patients were included. Disease control was obtained in 90/93 cases. Laryngeal preservation rate was 96.8%. Twenty patients had a local residual disease or recurrence after the first laser surgery, but 17 were salvaged (85%). Local residual disease and recurrence were more frequent in patients with advanced disease (T1b/T2), invasion of anterior commissure and "non‐safe" margins. Conclusion: The proposed follow‐up scheme might be a valuable option, but with caution for positive or unevaluable margins as the latter is an independent risk factor for local recurrence. An early laser excision procedure (eg, within the first two months after surgery) or an alternative strategy may be discussed in this situation. "Watchful observation" should be reserved for compliant patients only so that the risk of missing potential recurrences is minimised.